Physicochemical composition and quality parameters of almond and macauba almond oil (Acrocomia aculeata (jacq.) lodd) (Research, Society and Development, 2020)
The macauba almonds (Acrocomia aculeata) have aroused great economic and nutritional interest as they are a promising source of chemical compounds and oils with high oxidative stability. This study proposed to carry out the characterization of the physicochemical composition and to evaluate the quality parameters of the macauba almond, as well as to verify the amounts of fatty acids, peroxides and selenium present in the macauba's oil. This is a field and laboratory research of qualitative nature. Among the main results, high levels of ash (1.37 g/100g-1), proteins (12.12 g/100g-1) and fibers (11.31g/100g-1) were found in the almond, placing it in front of other oilseeds due to superiority of these nutrients. In the oil, a low presence of free fatty acids (2.30% w/w) and peroxides (0.56 meq Kg oil-1) was detected, indicating that this food has high oxidative stability. As for the selenium content, no significant presence of this mineral was identified in both foods. As a result, it is concluded that the almond and the oil of the macauba almond can be inserted in the market as a viable strategy aimed at people who wish to positively modify their diet, as they present satisfactory physicochemical characteristics and quality parameters.